Relationship of genetically modified crops with the environment and health of the Costa Rican human population - Espinoza, Ana M. (2004)
Genetic engineering and the food derived from genetically modified crops (GMCs) have been the center of debate worldwide, as has occurred historically with the advent of new technologies. Questions are derived from the potential impact of GMCs to the environment and the safety of the products to the consumers. In relation to the first inquiry, practice has been oriented to a case-by-case-study, according to the own characteristics of the GMC, in order to minimize its impact in the environment. Scientific studies in diverse latitudes of the world have demonstrated that GMCs in the market showed no adverse effects related to this issue. In relation to food derived from the GMCs, rigorous evaluation protocols have been developed and approved by FAO and WHO to guarantee the innocuousness of these products. Up to the moment, no contraindications for human health have been pointed out for the products that are available today in the market. In the particular case of Costa Rica, the country has established since the 90s a regulatory biosafety framework for the management of the GMCs, safeguarding the biodiversity of the country and the health of consumers. At the same time the country has made significant public and private investments in the field that allowed the country to obtain a leading position in biosafety in the region and genetic engineering research at national research centers. Any attempt to restrict or prohibit these activities in the country, will put in risk the previously described investment, will affect the generation of new knowledge for decision making and the leadership in the field, preventing the benefits derived from this promising technology.